Inflammatory gynecologic diseases - Amro, I. G.; Zaliznyak, V. O.; Амро, Ірина Геннадіївна; Залізняк, Владислав Олександрович (Zaporozhye state medical university, 2016)
The textbooks in gynecology used by the senior medical students according to the curriculum and study hours include the chapters about gynecologic diseases requiring emergency. The independent training with the textbook proposed now will help the senior students, obstetricians and gynecologists in future to learn this pathology better. The interns specialized in Obstetrics and Gynecology within the period of their studies during three years have to master their knowledge and skills based on the advanced studies of gynecologic emergencies. The data exposed in this textbook are aimed at this goal. The textbook is recommended to be used by the obstetricians and gynecologists in their practice.